O-32 Optimising diagnostic criteria for ulnar neuropathy at the elbow. Issue 7 (July 2019) - Pugdahl, Kirsten; Beniczky, Sándor; Tankisi, Hatice; Johnsen, Birger; Qerama, Erisela; Otto, Marit; Fuchs, Steffen; Fuglsang-Frederiksen, Anders
Abstract : Background: Different sets of electrodiagnostic criteria for ulnar neuropathy of the elbow have been published by the AANEM and recently by a Danish consensus group. This study assessed whether a modification of the two sets could increase diagnostic performance. Material and methods: The new set of criteria was derived by testing different combinations of the features in the current criteria. The optimal cut-off value for difference in conduction velocity (CV) between the elbow and forearm segments was determined using ROC curve analysis. The diagnostic accuracy was evaluated on 181 neurophysiological studies of the ulnar nerve from a mixed patient-group and the diagnostic reference standard was the consensus diagnosis based on all available clinical, laboratory, and electrodiagnostic information reached by a group of experienced Danish neurophysiologists. Results: The best performance were obtained in a set of criteria requiring both (a) More than 2 standard deviation (SD) slowing in CV at the elbow and (b) Absolute slowing in CV between the elbow and forearm segments of at least 12 m/s. The criteria had a very high sensitivity of 98.1% and a good specificity of 90.7%. Conclusions: The new criteria have an excellent diagnostic performance and are simple to use. Although the criteria are suggested by a single centre and evaluated on a rather small group of patients, there seems to be a potential for improving the criteria currently available. This will make electrodiagnosis an even more powerful tool for diagnosing ulnar neuropathy at the elbow.